Closing the Osteoporosis Care Gap in Hip Fracture Patients: An Opportunity to Decrease Recurrent Fractures and Hospital Admissions. (29th September 2011) - Byszewski, Anna; Lemay, Genevieve; Molnar, Frank; Azad, Nahid; McMartin, Seanna E.
Abstract : Background . Falls and hip fractures are an increasing health threat to older people who often never return to independent living. This study examines the management of bone health in an acute care setting following a hip fracture in patients over age 65. Methods . Retrospective chart review of all patients admitted to a tertiary health facility who suffered a recent hip fracture. Results . 420 charts of patients admitted over the course of a year (May 1, 2007–April 31, 2008) were reviewed. Thirty-seven percent of patients were supplemented with calcium on discharge, and 36% were supplemented with vitamin D on discharge. Thirty-one percent were discharged on a bisphosphonate. Conclusion . A significant care gap still exists in how osteoporosis is addressed despite guidelines on optimal management. A call to action is required by use of multifaceted approaches to bridge the gap, ensuring that fracture risk is minimized for the aging population.